THE ROLE OF INFORMATION AND DOCUMENTATION MANAGEMENT OFFICERS IN ENSURING ACCESS TO OPEN INFORMATION AT THE OFFICE OF THE GENERAL ELECTION COMMISSION OF NORTH LUWU REGENCY - Rusman, Karmila; Nur, Andi Cudai; Guntur, Muhammad; Fitri, Anisa (Universitas Negeri Makassar, 2025)
This study aims at the Role of Information Management and Documentation Officers (PPID) in Assuring Access to Information Disclosure at the Office of the General Election Commission (KPU) of North Luwu Regency. To achieve this goal, the researchers used data collection techniques through observation, interviews and documentation. The data that has been obtained from the research results are processed using qualitative analysis with data collection techniques, namely observation, interviews, and documentation. The data obtained from the results of the study were processed using data analysis techniques, data reduction, data presentation and conclusion. The results of the study show that the Role of Information Management and Documentation Officers (PPID) in Assuring Access to Information Disclosure at the Office of the General Election Commission (KPU) of North Luwu Regency is seen from the Role of Heroepoetri (2003), namely: (1) Role as Policy, (2) Role as Strategy, (3) Role as Communication. Assessment of the Role of Information Management and Documentation Officials (PPID) seen from the observations of researchers and the results of interviews between researchers and informants, it can be concluded that Open Access to Information can be said to be good. This is evident from the policies made in information services, strategies achieved and coordination with regional apparatus to provide public information services.